Rapport in Distance Education - Murphy, Elizabeth; Rodríguez-Manzanares, María A. (International Review of Research in Open and Distributed Learning, 2012)
Rapport has been recognized as important in learning in general but little is known about its importance in distance education (DE). The study we report on in this paper provides insights into the importance of rapport in DE as well as challenges to and indicators of rapport-building in DE. The study relied on interviews with 42 Canadian high-school DE teachers. Findings revealed that rapport is necessary in DE because of the absence of face-to-face communication. Challenges to building rapport relate to the geographic dispersion of students, the asynchronous nature of DE, teacher workload, limits of the software, teachers and students not seeing the need for rapport, and DE traditions. We identified six categories of rapport-building in DE as follows: Recognizing the person/individual; Supporting and monitoring; Availability, accessibility, and responsiveness; Non text-based interactions; Tone of interactions; Non-academic conversation/interactions. We break the categories into subcategories and provide indicators for each one. The indicators might also be used in contexts of DE teacher professional development as a springboard for discussion, or, more prescriptively, as guides to DE teacher behaviour. A follow-up study using a more fine-grained focus on specific indicators might provide insights into specific rapport-related behaviours.